PENGEMBANGAN BAHAN AJAR FLIPBOOK MANFAAT ENERGI KELAS IV DI SEKOLAH DASAR - Diana Rossa Martatiyana; Lina Novita; Ratih Purnamasari (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This study aims to produce flipbook teaching materials for theme 2, subtheme 2, the benefits of learning energy 1 in class IV at SDN Semplak 1 and to determine the feasibility of flipbook teaching materials. This development uses the ADDIE model. The research begins with a needs analysis, making a design, developing a flipbook teaching material design, then being validated by experts, revising the product, and conducting a limited trial (implementation). The total average value of the validation results of material, media, and language experts shows that flipbook teaching materials are very feasible to use with an average acquisition percentage of 91.90%. In the limited test stage, 29 students gave a very good response to the flipbook teaching materials used. Based on the results of the study, it was concluded that this flipbook teaching material was tested, interesting and very suitable for students to use for learning.